2007
DOI: 10.1080/00220380701466450
|View full text |Cite
|
Sign up to set email alerts
|

Oil abundance and violent political conflict: A critical assessment

Abstract: This paper addresses one of the empirical claims of the 'resource curse' argument, namely that oil abundance raises the probability of political violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 38 publications
0
36
0
2
Order By: Relevance
“…Their main results suggest that oil predicts wars not because it provides a source of finance for rebel groups but, more likely, high oil exports indicate a poor and fragile state, in which its military and institutional structures are not capable of effectively repressing the outbreak of armed insurrection as has happened, for example, in various sub-Saharan nations. The link between oil and civil war has been also analysed by Di John (2007), who shows how the correlation between civil war and the presence of oil is not robust. In oil rich nations where violent conflicts occur, oil is not necessarily the cause, but other factors, such as weak government, recent conflict, poor economic performances or war in a neighbouring state, tend to play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Their main results suggest that oil predicts wars not because it provides a source of finance for rebel groups but, more likely, high oil exports indicate a poor and fragile state, in which its military and institutional structures are not capable of effectively repressing the outbreak of armed insurrection as has happened, for example, in various sub-Saharan nations. The link between oil and civil war has been also analysed by Di John (2007), who shows how the correlation between civil war and the presence of oil is not robust. In oil rich nations where violent conflicts occur, oil is not necessarily the cause, but other factors, such as weak government, recent conflict, poor economic performances or war in a neighbouring state, tend to play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…While poor economic performance has undoubtedly been the experience in some situations, recent empirical case studies have shown that while this might be true in some countries it is not the case in others (Roe, et al 2004;DiJohn 2002). The obvious question is: why is this so?…”
Section: The 'Resource Curse' and Governance: A Papua New Guinean Permentioning
confidence: 98%
“…Referring to the contradictory empirical results of econometric studies, deficient databases, and the existence of various outliers-resource countries like Botswana, Chile or Norway, which are stable democracies and economically prospering-more recent literature on the resource curse has partly questioned the alleged resources-violence link (Hegre/Sambanis 2006;Bulte/Brunnschweiler 2006;Di John 2007). Several authors demand a further theoretical differentiation within the debate and suggest that the impact of certain contextual conditions is pivotal for the incidence or absence of the so-called resource curse.…”
Section: A Differentiated Approach Through the Inclusion Of Contextuamentioning
confidence: 99%